Drug Targeting and Nanotherapeutic Advancement in the Treatment of Rheumatoid Arthritis: Recent Progress in Drug Delivery Systems - Deshmukh, Rohitas (Current Pharmaceutical Biotechnology, 2025)
Pain and swelling in the joints, increased synovial thickness, and bone and cartilage degeneration are all symptoms of Rheumatoid Arthritis (RA). Anti-rheumatic medications, which are used in conventional treatment plans for RA, need high doses, frequent administration, and long-term use, all of which increase the risk of major adverse effects and low patient compliance. Drug Delivery Systems (DDS) have been developed for RA treatment in an effort to avoid these obstacles and improve clinical efficacy. There have been many successful experimental RA models using these techniques. There has been a notable uptick in the study of RA nanotherapies as a prospective improvement over conventional systemic therapy. In order to overcome the limits of traditional treatments, researchers have begun looking into nanotherapeutic approaches, notably drug-delivery nanosystems. The precise delivery and concentration of therapeutic drugs in the affected regions are made possible by the passive or active targeting of systemic administration. Several new DDS for treating RA have been addressed here. Therefore, nanoscale drug delivery devices increase drug solubility and bioavailability while decreasing the need for higher doses.
Keywords: Rheumatoid arthritis